PERANCANGAN BUKU CERITA BERGAMBAR SITI MANGGOPOH PAHLAWAN YANG TERLUPAKAN - YULIA RATRI ANANTA, Henra Afriwan, S.Sn., M.Sn. Dr. M. Nasrul Kamal, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The incident of resistanc kenagarian Manggopoh and vicinity in 1908 what is called the Manggopoh War whose against Dutch economic policy money tax “belasting” and other factors. The Manggopoh War led by a brave woman named Siti who succeeded in defeating 53 people Dutch troops, but she had to surrender later for his people at Manggopoh. The purpose of this design produced an illustrated story book to symbolize a struggle being fought with tittled “Siti Manggopoh Pahlawan yang Terlupakan”. The purpose of this illustrated story book is to identify as female warrior in West Sumatera, engendered a reading interest in children, and can take a good lessons from heroes’ stories.This theory is used as a supporter in the refining of the illustrated story book Siti Manggopoh pahlawan yang terlupakan. The design method used is the glass box method of rational, optimistic thingking without sentiment factors. This illustrated story book was created to reintroduce this heroic figure to children and also to inspire children to make changes, either in the form of leadership or in the attitude of achieving a goal. The result of this design use the main medium of an illustrated story book because it explains the actual plot of the story and the supported media used as x-banner, poster, t-shirt, bookmarks, mugs, and stikers.Keywords : Design, The Illustrated Story Book, Siti Manggopoh